Fire Safety Design for Tall Buildings - Fu, Feng (Milton : CRC Press, 2021)
Fire Safety Design for Tall Buildings provides structural engineers, architects, and students systematic introductions to fire safety design for tall buildings based on current analysis methods, design guidelines, and codes. It covers almost all aspects of fire safety design that an engineer or an architect might encounter--such as performance-based design the basic principles of fire development and heat transfer This book also sets out an effective way of preventing the progressive collapse of a building in fire, and it demonstrates 3D modeling techniques to perform structural fire analysis with examples that replicate real fire incidents such as Twin Towers and WTC7. This helps readers to understand the design of structures and analyze their behavior in fire.
OCLC-licensed vendor bibliographic record.
Keywords: Building, Fireproof; TECHNOLOGY / Construction / General; TECHNOLOGY / Fire Science